Viability of a technology-based education afterschool program - Sansolis, Evans B.; Leonoras, Carmenda S. (Technium Social Sciences Journal, 2021)
This research is a quantitative study that employed a descriptive research design to analyze the skillset gap by determining the level of importance of the technical skillset needed by the emerging Information Technology (IT) industry and the extent of technical skills acquired by State University and Colleges’ (SUCs) technology-based education programs graduating students in the Province of Iloilo. Likewise, it sought to provide baseline information on the viability of a Technology-based Education Afterschool Program (TEAP). This concept was based on the rationale that the Skills Gap Analysis and the provision of TEAP will effectively narrow down the IT skills gap. It will help SUCs’ technology-based education program graduating students acquire IT industry-standard skills in robotics, computer programming, system analysis, design, web development, game development, and mobile application development. Moreover, the researcher used a descriptive design for this study, wherein an expert validated descriptive survey was developed and utilized. The researcher also established the content of this expert-approved descriptive survey instrument based on the selected sixty IT-industry skills, organized into fifteen skillsets. This survey instrument includes general questions relating to the importance level of the IT mentioned above industry skills crafted based on the viewpoints of high-level IT-industry decision-makers and SUCs technology-based graduating students. Sixty-four respondents from the IT industry who were managers/supervisors/practitioners and four hundred technology-based education graduating students of SUCs were selected using stratified random sampling. The researcher statistically treated the obtained data using the Mean, Standard Deviation, and the T-test. The Mean Difference between the Technical Skillset needed by the IT industry in contrast to the Levels of Acquired Knowledge of the graduating students of technology-based education programs is the Skills Gap. Based on statistical inputs, the statistical findings revealed that the skillset “Knowledge in Internet-of-Things” was considered the top priority skillset needed by the IT industry. This skillset, however, is the least developed skillset of the SUCs technology-based graduating students. Therefore, “Knowledge in Internet-of-Things” earned the highest Skills Gap result amongst the fifteen IT-industry skillsets. Additionally, the T-test concluded a significant difference between the IT industry-standard technical skillset and the skillset acquired by SUCs’ technology-based education programs graduating students; and that this difference is not attributed to chance. In conjunction with this, the proposed plan to address the IT skillset gap includes developing TEAP for the skillset Knowledge in Internet-of-Things, which involves skills enhancement in the development of the IoT device, Connecting IoT device to the Internet, and Programming IoT Device.